Concurrent Enhancement of Multiple Properties in Reactively Processed Nanocomposites of Polylactide/Poly[(butylene succinate)‐co‐adipate] Blend and Organoclay1. Issue 5 (15th October 2013) - Ojijo, Vincent; Sinha Ray, Suprakas; Sadiku, Rotimi
<x xml:space="preserve">Abstract</x> Polylactide (PLA) and poly[(butylene succinate)‐co‐adipate] (PBSA) were reacted by being blended in a batch mixer in the presence of a chain extender, triphenyl phosphite (TPP), and two different types of organically modified clays—a montmorillonite clay (C20A) and a synthetic mica (MEE)—to enhance the thermal stability, impact toughness, and barrier properties of the PLA. An accelerated increase in the torque during processing indicated catalyzed chain‐extension reactions in the clay‐based compatibilized blends. The rate and extent of the increase in the chain extension/coupling were dependent on the type of organic surfactant used to modify the pristine clays. Enhanced chain extension/coupling and char formation resulted in dramatic thermal‐stability increases of 17 and 26 °C for composites with 2 and 6 wt% C20A loadings, respectively. Similarly, the oxygen and water‐vapor permeabilities were improved with the addition of the clays. At 4 wt% MEE loading, the oxygen and water‐vapor permeabilities were reduced by 60 and 50%, respectively. Unlike the MEE‐based blends, C20A‐based compatibilized blends resulted in higher toughness than the neat PLA due to the lesser crystallinity of the PLA component and enhanced chain extensions/coupling in the C20A‐based samples. Therefore, this work demonstrates the possibility of enhancing the thermal stability, toughness, and barrier properties of PLA in a one‐stage process through reactive blending with PBSA in the presence of clays.<inline-graphic xlink:href="ark:/27927/pgg5nq98bq8" content-type="mame201300306-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />